Construction of a highly effective self-repair corrosion-resistant epoxy composite through impregnation of 1H-Benzimidazole corrosion inhibitor modified graphene oxide nanosheets (GO-BIM). (December 2018) - Kasaeian, Mojtaba; Ghasemi, Ebrahim; Ramezanzadeh, Bahram; Mahdavian, Mohammad; Bahlakeh, Ghasem
Graphical abstract: Highlights: A highly effective corrosion resistant epoxy coating with excellent self-repair properties was fabricated. The BIM molecules were successfully adsorbed on GO nanosheets. Kinetics and thermodynamics of BIM adsorption were studied in details. The inclusion of 0.1% GO-BIM into the epoxy coating provided an effective active/passive corrosion protection system. Abstract: The aim of this study is to construct a highly effective corrosion resistant epoxy coating with excellent self-repair and active corrosion inhibition properties. For this goal, the graphene oxide (GO) nanosheets were non-covalently functionalized with 1H-Benzimidazole (BIM) molecules. The morphology and chemistry of GO-BIM composite were investigated by field emission scanning electron microscopy (FE-SEM), energy dispersive X-ray spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy. It was found from the electrochemical tests results that inclusion of 0.1% GO-BIM into the epoxy coating provided an effective corrosion-resistant system with remarkably enhanced barrier and active inhibition properties, simultaneously.